2011
DOI: 10.1111/j.1365-313x.2011.04537.x
|View full text |Cite
|
Sign up to set email alerts
|

A revised mineral nutrient supplement increases biomass and growth rate in Chlamydomonas reinhardtii

Abstract: SUMMARYInterest in exploiting algae as a biofuel source and the role of inorganic nutrient deficiency in inducing triacylglyceride (TAG) accumulation in cells necessitates a strategy to efficiently formulate species-specific culture media that can easily be manipulated. Using the reference organism Chlamydomonas reinhardtii, we tested the hypothesis that modeling trace element supplements after the cellular ionome would result in optimized cell growth. We determined the trace metal content of several commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
233
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 303 publications
(245 citation statements)
references
References 76 publications
1
233
0
Order By: Relevance
“…Nutrient-deficient media were prepared as follows. NH 4 Cl was omitted in nitrogen-free TAP; MgSO 4 was omitted in sulfur-free TAP; ZnSO 4 was replaced with ZnCl 2 ; potassium phosphate was replaced with 1 mM KCl in phosphorus-free medium (46); iron-free Hutner's trace element solution was supplemented with 0.25 M FeCl 3 for low iron medium (47) and zinc-free Kropat's trace elements for zinc-deficient TAP medium (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient-deficient media were prepared as follows. NH 4 Cl was omitted in nitrogen-free TAP; MgSO 4 was omitted in sulfur-free TAP; ZnSO 4 was replaced with ZnCl 2 ; potassium phosphate was replaced with 1 mM KCl in phosphorus-free medium (46); iron-free Hutner's trace element solution was supplemented with 0.25 M FeCl 3 for low iron medium (47) and zinc-free Kropat's trace elements for zinc-deficient TAP medium (21).…”
Section: Methodsmentioning
confidence: 99%
“…Although biomass from terrestrial plants can be processed and used as a feedstock for generating alcohols and other fuels (8) oil from photoautotrophically grown algae or seeds represents another fuel source, with algae offering distinct advantages over traditional oil crops (9,10). The green alga Chlamydomonas reinhardtii accumulates increased amounts of triacylglycerols (TAGs) 5 under conditions of growth-inhibiting macro-or micronutrient deficiency such as sulfur (11), nitrogen (12)(13)(14)(15)(16)(17)(18)(19)(20), phosphorus (15), zinc, or iron deficiency (21) or other growthinhibiting stressors such as high salt (22) or high light (23). With a sequenced genome (24) and the potential for application of metabolic engineering (25), C. reinhardtii is a powerful reference organism for discovering green algal TAG biosynthetic pathway(s) and the ways in which they are regulated by nutrient deprivation.…”
mentioning
confidence: 99%
“…Chlamydomonas was grown using Tris acetate phosphate (TAP) media (Gorman and Levine, 1965) with mineral nutrient supplements (Kropat et al, 2011). A working stock of Chlamydomonas was maintained on solid TAP media containing 1.6% Bacto agar (Difco) and was subcultured biweekly.…”
Section: Methods Plant Material Growth Conditions and Uv-b Irradiationmentioning
confidence: 99%
“…Chlamydomonas cultures Strains were grown in acetate-containing (TAP) medium or minimal (HSM) medium as described in (Harris et al, 2009), however a revised trace metal recipe was used as found in (Kropat et al, 2011). Cells were grown in 100 ml cultures, at 25°C, shaking at 110 rpm using illumination at 15 µmol photons m Plasmid design The pASapI vector, described in (Economou et al, 2014), was used for the introduction of the CYP79A1 coding sequence into the chloroplast genome.…”
Section: Methodsmentioning
confidence: 99%